Motivación: perspectivas teóricas y algunas consideraciones de su importancia en el ámbito educativo - Naranjo Pereira, María Luisa (2009)
This article has for objective to review the concept of motivation, its historical development, and the three main approaches about it: behavioral, cognitive and humanistic, and some important aspects of the motivation on the educational ambit. The first approach emphasizes that people are motivated by the profit or reward they can receive. The humanistic underlines the qualities of human beings, their ability to grow and their freedom of choice. This approach looks at the motivational theories: Hierarchy of Needs by Maslow, Existence, Relation and Growth Theory by Alderfer and McClelland's Theory of Needs. The cognitive approach points out that the thought we think might happen determines what happens. Thoughts guide motivation. From this approach we review the Expectations Theory of Vroom, the Equity Theory Adams and the Model Setting Goals and Objectives from Trechera. Especially in the field of education examines the relationship between emotion and motivation, and the relationship between the Theory of Attributions and academic performance. Are some reasons that can guide student behavior and finally explores the intrinsic and extrinsic motivation and its influence in the academic performance of the students.